TRUST ADVANTAGE IN EXPORT PERFORMANCE OF SMEs FOR FURNITURE EXPORTERS IN JEPARA - Samsul Arifin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study is to analyze the trust advantage in export performance of SMEs for furniture exporters in Jepara. This study used qualitative approach to analyze the theory, build facts, show the relationship between variables, provide statistical descriptions, estimate and predict the results. In addition, it analyzes trust in partnership and trust in export performance. The population sampling taken are 307 furniture companies in Jepara which are exporters in the international furniture trade market. Structural Equation Model was used to analyze structural relationship between trust variable and latent constructs as indicators. The results show that trust has a role to enhance asymmetric partnership formation in order to create an organizational trust building where the inter-organizational and inter-personal trust interplay is scrutinized. The existence of strong positive relationships between trust–commitment, trust–export performance and commitment–export performancehas implications for export marketing managers and researchers with respect to managing cross-border export–import relationships categorised by trust, commitment and exportperformance. It shows that the intensity of competition, trust, commitment, export performance, by Structural Equation Modeling, identifies that trust influences commitment and export performance positively, and commitment has a positive effect on export performance of SMEs for furniture exporters in Jepara.